(untitled) (Ameghiniana, 2014)
The fishes occurring in the Anta Formation outcrops in the Quebrada de La Yesera (Salta, Argentina) are assessed as paleoenvironmental indicators. According to the ichthyofauna and geologic evidence, the fossiliferous beds were deposited near sea-level, the lake was fresh-water, and had no marine influence at this moment. Taxa recorded lo the moment are clupeids, cichlids and serrasalmine characids. All these teleosts are typical of basins of low altitude located in eastem Argentina. None of them inhabit the area today. The modification in the distribution of those fishes was occasioned by tectonic changes that greatly modified the ecological factors. The recent icthyogeographic pattern at this latitude developed after Serravallian-Tortonian boundary (around 10-11 Ma ); after the Colloncuran-Mayoan of the local chronostratigraphic standard. The environmental changes included the end of the large Paranian engulfment and important modifications in topography. The record of Cretaceous fishes in the area is refuted and the first record in South America of an almost complete skeleton of a pacú (Teleostei, Characifonnes, Serrasalminae) is reported.